A Description of Routes out of the Labor Force for Workers in Sweden - Daniel Hallberg (Uppsala University, Department of Economics, 2003)
This paper collects and reviews information about routes to retirement and exits from the labor force by older workers in Sweden. It gives a concise survey of rules of the major retirement schemes covering disability, sickness and unemployment. Usinglongitudinal micro data from the period between 1992 and 1999, it also studies alternative measures of retirement, joint retirement behavior of spouses, transition path probabilities, and successive exits in terms of a reduction in working time from fulltime to part-time employment.
urn:nbn:se:uu:diva-4495
Keywords: J14; J21; J22; J26; 330; Retirement; pension schemes; unemployment; sickness; disability; working hours; longitudinal individual data set; register-based income data; transition matrix; Altersgrenze; Ruhegehalt; Arbeitslosigkeit; Krankheit; Arbeitszeit; Schweden